Athlete leadership in football - Loughead, T. M.; Duguay, A. M.; Hoffmann, M. D. (Football Psychology - From Theory to Practice, 2019)
Football players and managers recognize the importance of having strong leadership for team success. Managers believe that strong leadership from their athletes is necessary for teams to function optimally (Bucci, Bloom, Loughead, & Caron, 2012; Gould, Guinan, Greenleaf, & Chung, 2002). This source of leadership is known as athlete leadership and is viewed as an athlete who occupies a formal or informal leadership role within the team and influences team members to achieve a common goal (Loughead, Hardy, & Eys, 2006). This definition highlights two types of leadership roles. The first is a formal athlete leadership role, where players are designated to a leadership position by the club (e.g. team captain, vice-captain). The second is an informal athlete leadership role where players are perceived by others as being instrumental without being officially appointed by the club as a leader. When leadership on a football team is considered from this perspective, all footballers have the opportunity to engage and provide leadership to their teammates. In fact, research has shown that the responsibility of leading a team does not rest solely on the shoulders of the team captain; rather leadership is shared amongst a group of players. Further research has shown that athlete leadership is related to a host of team dynamic variables including cohesion and collective efficacy. Given these benefits, research has shown the importance of developing athlete leadership and how peer mentoring can be optimally fostered within a team environment.